Assessing Oral Communication Skills of Students in Business Administration Department - ASTUTY, Ani Dyah (Research and Innovation in Applied Linguistics, 2023)
This research article presents an assessment of the oral communication skills of students in the Business Administration Department. A questionnaire was used to measure 95 students' self-perceived ability in oral communication for various activities. The study aimed to identify areas of strengths and weaknesses in students' oral communication skills and highlight potential areas for improvement. The findings revealed that students rated themselves low in the category of "Providing training through discussions, workshops," suggesting a need for focused attention in this particular skill area. These results have implications for curriculum development and instructional strategies, emphasizing the importance of incorporating targeted training methods to enhance students' oral communication skills in the Business Administration program